Collagen Stimulators in Body Applications: A Review Focused on Poly-L-Lactic Acid (PLLA) - Christen MO (Dove Medical Press, 2022)
Marie-Odile Christen Behavior, Paris, FranceCorrespondence: Marie-Odile Christen, Behavior, 27 Avenue Marceau, Paris, 75116, France, Tel +33 680998336, Email christen.marieodile3@gmail.comAbstract: The number of aesthetic procedures performed worldwide continues to grow together with an increase in the population seeking the restoration or preservation of a youthful appearance. Requests for non-surgical body rejuvenation are increasing. Patients are looking for safe and effective minimally invasive aesthetic procedures. Soft-tissue dermal fillers can meet these expectations. Based on the beneficial outcomes of these treatments in many facial areas, a new trend is developing to target body areas. Different dermal fillers are available and include collagen stimulators initially developed to restore facial volume. Furthermore, they are associated with long-lasting efficiency, a high level of patient satisfaction and a good safety profile, with mainly minor adverse events reported. In appropriate conditions of use, they are now used for body rejuvenation in clinical practice. Their use is expanding and allows addressing various issues including volume loss, skin laxity, cellulite, striae distensae and wrinkles. This review focuses on poly-L-lactic acid (PLLA), used in the first collagen stimulator and one of the most investigated in facial and in off-facial body applications. The available published data, although still limited, are presented by body area, neck and chest, buttocks, abdomen, upper arms, thighs, knees, and hands. Key features of the concerned zones and the main clinical signs affecting the body part as well as the injection modalities are provided along with the aesthetic results. This represents the state of the art on which to base further developments necessary for optimal and safe outcomes of treatment with the PLLA-based collagen stimulators and others in this class for body rejuvenation.Keywords: poly-L-lactic acid, PLLA, volume augmentation, body contouring, dermal filler, collagen stimulator, buttocks, body rejuvenation, skin laxity, skin quality